If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -8x = 86 + -36x Solving 8 + -8x = 86 + -36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36x' to each side of the equation. 8 + -8x + 36x = 86 + -36x + 36x Combine like terms: -8x + 36x = 28x 8 + 28x = 86 + -36x + 36x Combine like terms: -36x + 36x = 0 8 + 28x = 86 + 0 8 + 28x = 86 Add '-8' to each side of the equation. 8 + -8 + 28x = 86 + -8 Combine like terms: 8 + -8 = 0 0 + 28x = 86 + -8 28x = 86 + -8 Combine like terms: 86 + -8 = 78 28x = 78 Divide each side by '28'. x = 2.785714286 Simplifying x = 2.785714286
| 3(1+6n)=-19+7n | | 13(x+6)=11 | | 18-4x=2(1+6x) | | 10-3x=15x+2x | | 5/3x+1/3x=71/3+8/3x | | -5+7x=5+5x | | 5/3x+1/3x=71/3 | | 9+n=-1+6n | | 2x^2-8bx=-6b^2 | | 24=-8n | | M-(5-2m)-(4m+11)=5m-13 | | 34(x+2)=-1 | | 8a+6(a+7)=6(3a+7)+8 | | x+x+.56+.74=10.41 | | -3(1-8n)-8(4n-1)=61 | | 3x^2-15+x^2+x=90 | | b=65(10+9)w | | 11/14-2/10 | | 6z(z^2-1)=0 | | b=65(10+9) | | 10=1.25x | | 5(x-2)-4x=6+3x | | -3t+7u= | | 9n-9=-90 | | 0=6/7y | | .5x+5=6x+20 | | 8(7-4v)-8=-208 | | -6-(-3)=3 | | 5x+18=2(2x+5) | | 3x-9=2x+12 | | 24x-36=-6x+24 | | 6w+4=2-5(3w-1) |